Interior design of commercial play areas in selected malls in Metro Manila in terms of accessibility and mobility for children - Cruz, Catherine Joyce DM.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The study aimed to evaluate the interior design of commercial play areas in selected malls with regards to accessibility and mobility for children. Proxemics served as the guiding theory in understanding the relation of interior design to the use of space, child behavior, accessibility and mobility. These two dependent variables, accessibility and mobility, were also perceived to have intervening variables such as size, activities, materials, child behavior, crowding and territoriality. This study employed the multiple case study approach and data gathering methods such as observation, interview, and photo documentation were utilized. A purposive sampling design was applied in selecting the four (4) commercial play areas in malls that were studied, and categorized under middle end and high end commercial spaces. Data gathering was completed within two weeks, where in two days were alocated per play area in order to observe during peak hours and non peak hours. The study reveals that regardless of being classified under middle end or high end spaces, play areas in malls generally provide adequate floor spaces for children's mobility, but insufficiency with regards to the measurements of clearance or accessibility. However, since the children in this study focus more on playing and the novel aspects of their environment, they adapt to the spaces regardless of the provisions. The children in this study also treat intimate spaces as a form of camaraderie rather than difficulty, and crowding territoriality as an element in play. The interior design of commercial play areas also had a role in providing safety through materials, avoiding obstructions, and increasing ease in space utilization. With regards to safety, accessibility and mobility remain an important aspect in order to handle problem spaces and decrease chances of incidents.
Thesis (BS Interior Design)--University of the Philippines Diliman, June 2016.
Keywords: Playgrounds -- Philippines -- Designs and plans